Handbook of ocean wave energy - Pecher, Arthur; Kofoed, Jens Peter (Springer Open, 2017)
"Handbook for Ocean Wave Energy aims at providing a guide into the field of ocean wave energy utilization. The handbook offers a concise yet comprehensive overview of the main aspects and disciplines involved in the development of wave energy converters (WECs)"--Page v.
Keywords: Ocean wave power -- Handbooks, manuals, etc.; Ocean energy resources -- Handbooks, manuals, etc.; elektronické knihy; electronic books